The Effectiveness of Life Skills Training on Anxiety Sensitivity, Psychological Empowerment, and Soldiers' Anger - Abbas Shahverdi; Sara Saedi; Mohsen Razani (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objectives: The military personnel are more exposed to psychological harm than civilians. Therefore, the present study seeks to investigate the effectiveness of life skills training on anxiety sensitivity, psychological empowerment, and anger among soldiers. Materials and Methods: In a semi-experimental design with pretest-posttest with control group, 60 soldiers from the garrison of Shahid Javan-e-Pasha air defense group in Khondab city were selected using convenience sampling method and assigned into two groups of experiment and control. At first, anxiety sensitivity questionnaires, standard psychological empowerment questionnaire, Spielberger's Standard Anger Questionnaire were used for each group. Then, life skills training were provided to the experimental group and after the completion of the training program, a post-test was performed. The data were analyzed using multivariate covariance analysis via SPSS software version 22. Results: The mean (SD) score of the psychological empowerment of the experimental group was 63.4 (17.2) in pre-test, which increased to 80.2 (11.7), P<0.01; however, the mean (SD) score of the control group was 61.7 (3.5) in the pre-test, which was 64.7 (6.3) in the post-test, which was not statistically significant. The mean (SD) score of the anxiety sensitivity of the experimental group was 54.5 (2.8) in the pre-test, which decreased to 48.9 (1.6) in the post-test, P<0.01; however, the mean (SD) of the group the pre-test was 53.3 (5.8), which was 52.9 (6.4) in the post-test which was not statistically significant. The mean (SD) score of anger in the experimental group was 27.7 (7.7) in the pre-test, which decreased to 22.7 (9.1) in the post-test (P<0.01); however, the mean (SD) of the control group in the pre-test was 27.5 (5.5), which was 27.9 (5.8) in the post-test, which was not statistically significant. Conclusion: The study showed that life skills training increased psychological empowerment and decreased the anxiety sensitivity and anger among soldiers. DOI: http://doi.org/10.22037/ch.v7i2.25065